(untitled) (Fiep Bulletin - online, 2020)
Abstract: The aim of this study was to investigate the evolution of pole dance fitness to the present day and its future inclusion as a sport modality. The pole dance fitness corresponds to a sports modality concretized by means of gymnastic movements in vertical mast. The purpose of this study was to show the reasons why women and men seek Pole Dance Fitness as a daily practice and describe how regular practitioners perceive the inclusion of Pole Dance Fitness as a future sports and Olympic modality. The methodology adopted was the review of literature and field research with the adoption of a questionnaire for qualitative analysis, and it is classified as an exploratory research that intends to know the subject and to deepen existing knowledge. The study population analyzed refers to regular practitioners of the modality being our sample of a total of four adults, being two men and two women practicing Pole Dance Fitness. The results of the study indicate that the practice of Pole Dance for informants has contributed to several benefits related to health, well-being and better physical conditioning. Although the practice of Pole Dance has evolved, there is still a lot of prejudice, especially in relation to practicing men, but several people perceive it as a serious sport that must be recognized and achieve visibility in the sporting and Olympic context. It is concluded that the practice of pole dance promotes a better quality of life and also contributes to better physical fitness.